AoI-oriented low-energy-consumption information collection and transmission scheduling mechanism for emergency UAV networks - Yuming ZHANG; Lianming XU; Siyuan YIN; Linrun JIANG; Li WANG; Aiguo FEI (Tongxin xuebao)
To address the information collection and aggregation issue in emergency scenarios characterized by the lack of public infrastructure and unstable satellite signals, an information timeliness-oriented information collection and transmission scheduling mechanism was proposed for emergency unmanned aerial vehicle (UAV) networks where information collection and transmission capabilities were constrained by energy consumption.Considering the age of information (AoI) as the metric and constraint of information timeliness, a stochastics optimization problem was constructed with the objective of minimizing UAV information collection and transmission energy consumption.By resorting to the Lyapunov optimization technique, virtual queues were established to impose information timeliness constraints on queue lengths, and the original problem was decoupled into two sub-problems, information collection and transmission scheduling, with the premise of ensuring system stability.Corresponding heuristic algorithms were proposed for each sub-problem.Simulation results demonstrate that the proposed algorithm outperforms conventional queue scheduling approaches in convergence rates and system energy consumption with guaranteed information timeliness.